Parameter Kualitas Air untuk Budidaya Ikan Patin (Pangasius pangasius) di Karamba Sungai Kahayan, Kota Palangka Raya - Infa Minggawati; - Saptono (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
The Research on water quality parameters for the cultivation of patin fish (Pangasius pangaisus) in cage in the Kahayan River, aims to determine whether there are changes in water quality for each parameter were observed from March 2011 until March 2012. The results showed the water quality in Kahayan River especially in the fish cages area from March 2011 to March 2012 shows a decrease in water quality parameters: temperature, pH, DO, CO2, ammonia and brightness. This decrease is caused due to high rainfall in 2011 than in 2012 but it is a human activity along the Kahayan River. Although a decline in water quality around fish cages in the Kahayan River, was not too disturbing fish cultivation in the Kahayan River especially for the month of March 2011 until March 2012, meaning that the water quality can still be tolerated by fish.